Pengembangan E-modul Berbasis Model Pembelajaran Kooperatif Learning : Tipe Teams Games Tournament (TGT) Pada Materi Fungsi Kuadrat - Sahrain, Maryam; Pomalato, Sarson W.Dj; Oroh, Franky Alfrits (Pendidikan Matematika FKIP Universitas Mataram, 2025)
The purpose of this study is to produce a quality interactive learning E-module with a cooperative learning model of the Teams Games Tournament (TGT) type on the quadratic function material in class X of SMA Negeri 7 North Gorontalo. This study is a Research and Development study with an ADDIE approach model consisting of 5 stages, namely, Analysis, Design, Development, Implementation and Evaluation. The data in this study were collected using several instruments, namely, media and material expert validation questionnaires to assess the level of validity, as well as student response questionnaires to measure the practicality of the developed E-Module. The results of the study were based on the assessment of the quality of media and material, in accordance with the validation carried out by media experts and material experts separately, namely 71.52% and 60.51%, with valid criteria. And the results of student responses obtained a score of 80.06% with very practical criteria. This indicates that the E-Module based on the cooperative learning model of the teams games tournament (TGT) type meets the criteria of feasibility and practicality for application in learning.